2018
DOI: 10.1002/hrm.21936
|View full text |Cite
|
Sign up to set email alerts
|

Women's career equality and leadership in organizations: Creating an evidence‐based positive change

Abstract: Research on women's career equality and leadership is growing in importance for advancing social justice, equal employment opportunity, and global and national economic goals. Despite the increased attention being paid to gender equality for decades, progression has slowed or stalled around the globe, in many countries, such as United States. The goal of this special issue is to address the persistent research‐to‐practice gap in developing and implementing practical solutions for a positive change to advance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 65 publications
1
30
0
2
Order By: Relevance
“…A national approach to mentorship programmes may help fill the void in mentorship. [50][51][52] A redesign of the daily work, career advancement and scholarly demands could attract more women to surgery. [51][52][53][54] Shifting the surgical profession to support a work-life balance may encourage women to enter the profession.…”
Section: Discussionmentioning
confidence: 99%
“…A national approach to mentorship programmes may help fill the void in mentorship. [50][51][52] A redesign of the daily work, career advancement and scholarly demands could attract more women to surgery. [51][52][53][54] Shifting the surgical profession to support a work-life balance may encourage women to enter the profession.…”
Section: Discussionmentioning
confidence: 99%
“…HRD researchers also have emphasized the importance of critical HRD and advocated for research on diversity, inclusiveness, gender differences, spirituality, feminist leadership, sexual orientation, and transformational leadership (Baek & Kim, 2017; Rocco, Munn, & Collins, 2018). HRD research has examined veterans and their transitions from military to civilian careers (Minnis, 2017), explored the use of triple-loop learning to manage diversity (Kwon & Nicolaides, 2017), proposed diversity education as a means of advocating for inclusiveness and diversity (Hite & McDonald, 2010), delineated the research-to-practice gap in women’s career equality (Kossek & Buzzanell, 2018), identified disability as a form of diversity to be addressed by HRD (Nafukho, Roessler, & Kacirek, 2010), and demonstrated that opportunity, diversity, and inclusive employment practices are beneficial for both workers and organizations (Bourke et al, 2017).…”
Section: Adaptations and Advances In Hrdmentioning
confidence: 99%
“…Our findings contribute to a better understanding of why women may refrain from, or choose to, apply to certain career opportunities. Finally, following calls for HR management research to foster meaningful change for women in the workplace (Kossek & Buzzanell, 2018), this work allows us to bridge the research‐practice gap and to derive empirical knowledge to help HR managers and organizations in their pursuit of increasing gender diversity, especially in leadership.…”
Section: Introductionmentioning
confidence: 99%